Pedestrian detection with an interlaced chirp sequence concept in automotive radar - Thurn, Karsten; Heuer, Michael; Li, Gang; Max, Stephan; Meinecke, Marc Michael; Vossiek, Martin (16th International Radar Symposium, IRS 2015, 2015)
In this paper the application of the interlaced chirp sequence (ICS) concept in pedestrian detection is examined. The ICS waveform and range-Doppler signal processing are described and the resulting system parameters are deduced. The ICS waveform exhibits good resolution and range properties and lends itself well for pedestrian detection. Measurements with a 24 GHz radar system show good result
lhft_intern.bib::Thurn2015a
Keywords: Automotive applications; frequency modulation; radar detection; radar signal processing